The Control of Public Resources by the Controller of the Executive Power of Ceará State:: the actions of the Comptroller and General Ombudsman of the State of Ceará from 2006 to 2010 - Melo, Rogério Mourão (2014)
The current democracy is fertile ground to plant the seed of participation of society, both in the choice as in the monitoring of public policies. This is due to the constant changes especially in relation to technology tools, essential in the development of gear. However, in the face of constant changes in a globalized world institutions whether public or private, must adapt to new realities and follow in pursuit of their goals. This was due to the crisis of the Welfare State that has brought profound changes in the world economy and consequently caused the state to spend as we see profound changes that become agile and able to meet the needs of citizens. Therefore, it was necessary to create tools that would help citizens in seeking transparency in the implementation of public policies. In this context arise Comptrollers, organs that help the powers that be in the achievements of its objectives, with assignments inform unconformities control systems, recommend best management practices and create conditions for social control. Thus, this work aimed to expose the actions that the Comptroller and Ombudsman of the State of Ceará held in the period from 2006 to 2010 in the fight against waste of public funds in aid to social control and improvement of internal control, showing new management tools within the Executive Branch of the State of Ceará and the difficulties encountered in implementing these actions.